2018
DOI: 10.1111/gove.12364
|View full text |Cite
|
Sign up to set email alerts
|

Explaining institutional amnesia in government

Abstract: This article explains why different government agencies experience variations in organizational memory loss. It first explains institutional amnesia theoretically by expanding the formal‐institutional view of organizational memory to include agential and structural‐contextual properties, revealing a broader range of novel explanations for amnesia. Institutional amnesia is then explained empirically through an international analysis of memory loss in four Westminster systems (Australia, Canada, New Zealand, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…An organisation may also be so focused on particular priorities that it blinds itself to other issues-in effect forgetting how to see, interpret and act upon them (Vetzberger 1998;Stark 2019). A study by Zegart (2007) of the CIA prior to the 9/11 attacks found an organisation unable to acknowledge and act on threats from Al Qaeda because it was still stuck in a Cold War mindset.…”
Section: Public Organisation-driven Inactionmentioning
confidence: 99%
“…An organisation may also be so focused on particular priorities that it blinds itself to other issues-in effect forgetting how to see, interpret and act upon them (Vetzberger 1998;Stark 2019). A study by Zegart (2007) of the CIA prior to the 9/11 attacks found an organisation unable to acknowledge and act on threats from Al Qaeda because it was still stuck in a Cold War mindset.…”
Section: Public Organisation-driven Inactionmentioning
confidence: 99%
“…The neglect of history can also be a consequence of a wilful disinterest in learning about the past. This may be because confronting the past will challenge powerful interests, involve reforming the status quo or, more commonly, create political problems for incumbents and contemporary policies (Stark 2019). Thus, amnesia can be created through a simple unwillingness to interrogate the past because that means challenging dominant norms in the present.…”
Section: What Causes Institutional Amnesia?mentioning
confidence: 99%
“…Although they are also subject to the whims of external funding, long-running centres will have significant levels of institutional memory. Indeed, specialisation and expertise within an organisation is often an indicator of the likelihood of strong memory (Stark 2019). However, other bodies also have untapped stores of external memory.…”
Section: Use External Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Forms of memorialization, particularly in relation to traumatic events that inquiries have investigated, offer opportunities to recall past lessons, historical stories or the traditions of an agency (Linde ). Knowledge can also be recalled via training and human resource development practices within policy‐making agencies (Stark ) or via the creation of accountability mechanisms, specifically calibrated to inquiry‐driven reforms, which can ensure that agencies do not forget past failures (Stark ). Indeed, oversight is included in the model precisely because it connects with knowledge institutionalization and recall.…”
Section: The Location Of Failure: a Lesson‐learning Mapmentioning
confidence: 99%